Experimental and comparative study of metal hydride hydrogen tanks - Souahlia, A.; Dhaou, H.; Askri, F.; Sofiene, M.; Jemni, A.; Ben Nasrallah, S. (International journal of hydrogen energy, 2011)
Hydrogen, as an energy carrier, is a solution seriously considered at worldwide scale to enable renewable energy to be a part of our quotidian. Several challenges remain to produce, to store and to use hydrogen effectively. In our laboratory, we are interested in the discipline of hydrogen storage which is the subject of this paper. Two hydrogen storage tanks based on metal hydrides were built at the laboratory respecting a simple and modular design in a purpose of getting useful knowledge about the similarity elements of metal hydride tanks relevant in the prediction of a larger size storage unit behaviour. A description of the tanks is presented and an investigation of the parameters influencing the hydrogen storage performance is done. ► The storage of hydrogen in metal hydride vessels is influenced by the heat transfer. ► The kinetic of the two reactors studied depends on the temperature and the pressure. ► The filter decreases the hydrogen flow in the case of the absorption.